EVALUASI KEAMANAN DAN PRIVASI SISTEM REKAM MEDIS ELEKTRONIK: STUDI KASUS DI RUMAH SAKIT WAVA HUSADA - Soraya, Soraya; Oktoriyani, Ervita Nindy; Mawan, M. Syafiudin Aris (Malang: Sekolah Tinggi Ilmu Administrasi Malang, 2025)
Hospitals, as healthcare service institutions, bear a significant responsibility in ensuring patient data security, particularly through the implementation of electronic medical records (EMRs). Electronic medical records, as regulated by the Indonesian Ministry of Health Regulation (Permenkes) No. 24 of 2022, are electronic documents that record patient identity, examinations, treatments, and other medical services. The implementation of EMRs requires management aligned with information security standards such as ISO/IEC 27001:2013, encompassingconfidentiality, integrity, and availability. This study aims to evaluate the security and privacy of the electronic medical records system at Wava Husada Hospital, Malang. A qualitative descriptive approach was employed to understand the application of security principles, including confidentiality, authentication, access control, and data integrity. Data were collected through observations, interviews, and documentation, which were then analyzed in-depth. The findings indicate that Wava Husada Hospital has implemented security mechanisms such as authentication, access rights restrictions, and data backup systems. Additionally, the aspects of confidentiality and data integrity have been well-managed through policies like the use of unique passwords and supervised data deletion by authorized personnel. These findings provide valuable insights into the efforts of healthcare facilities to safeguard patient privacy and comply with applicable regulations, while also serving as a reference for enhancing information security systems in other healthcare services.